Diagnosis of precancerous lesions of the breast - D. I. Kebalo; N. P. Miroshnykova; O. P. Shershniova; S. M. Pashchenko; E. D. Zvantseva (Zaporožskij Medicinskij Žurnal)
The purpose of this work is to determine the optimal markers for clarifying the degree of proliferative activity in benign breast lesions, which can be used in surgical treatment planning.